CALCULATION THE PROBABILITY OF BANKRUPTCY FOR SHARIA INSURANCE COMPANIES USING THE MONTE CARLO METHOD - Sofia, Aya
In industrial and financial mathematics, bankruptcy theory is employed to analyze the dynamics and solvency ratios of insurance products influenced by various risks. This study aims to develop a new risk model for hybrid takaful (Islamic insurance) and to establish computational procedures for calculating the bankruptcy probability of insurance companies using the monte carlo method. The hybrid takaful business model implements wakalah contracts for underwriting and mudharabah contracts for investment. The primary distinction from conventional insurance lies in the qard hasan loan facility, provided by shareholders as an interest-free loan to the policyholder's fund in case of a deficit, to be repaid when the company generates profits. This final project conducts numerical simulations to analyze the impact of parameters in the hybrid takaful model on bankruptcy probability. Adding funds to the investment account when the company already has initial capital can increase the company's survival probability by 7.57%. Conversely, the optimal distribution of initial funds to the surplus account can enhance the company's survival probability by 19.64%. The findings also indicate that the proposed hybrid takaful insurance model outperforms the conventional model in terms of bankruptcy likelihood.